Diethyl [(5-chloro-2-hydroxyanilino)(4-chlorophenyl)methyl]phosphonate - Krishnaiah, M.; Babu, V. H. H. Surendra; Prasad, G. Syam; Reddy, C. Suresh; Puranik, Vedavati G. (Acta Crystallographica Section E-Structure Reports Online, 2009)
In the title compound, C17H20Cl2NO4P, the P atom is bonded in a distorted tetrahedral environment. The dihedral angle between the two benzene rings is 80.5 (1)degrees. In the crystal structure, intermolecular O-H center dot center dot center dot O and N-H center dot center dot center dot O hydrogen bonds link pairs of molecules into centrosymmetric dimers. These dimers, are in turn, linked by weak intermolecular C-H center dot center dot center dot O hydrogen bonds into one-dimensional chains along [010]. Additional stabilization is provided by very weak C-H center dot center dot center dot Cl interactions.